Overview of Pregnant Women's Knowledge about ANC - Ni Ketut Citrawati; I Gusti Ayu Putu Satya Laksmi (Indonesian Journal of Global Health Research, 2021)
The maternal mortality rate in Indonesia is still dominated by the three main causes of death, namely bleeding, hypertension in pregnancy and infection. Antenatal services are health services by health workers for mothers during their pregnancy in accordance with the standards of antenatal care set out in the Midwifery Service Standards (SPK). In 2017 there was a decrease and the difference between K1 and K4 coverage was 7.3%. The purpose of this study was to determine the characteristics of pregnant women including: age, education and occupation at the Tampaksiring II Health Center. This type of research is a quantitative research with a cross-sectional approach that uses a descriptive design. The data collected by giving quiestionaire to respondences. The data analized by using SPSS programe. The population in this study were all pregnant women who visited the Puskesmas Tampaksiring II and the sample in this study was 30 people. The results of this study showed that from 30 respondents 25 (83.3%) knowledge of pregnant women about antenatal care was good, while 5 (16.7%) knowledge of pregnant women about antenatal care was poor. According to Notoadmojo, the older the mother, the more knowledge she has. Mothers in their late teens will have less knowledge and experience because at this age mothers still do not have extensive experience so that it affects mother's knowledge about health, especially about Ante Natal Care (ANC). It is expected for pregnant women to increase the knowledge of pregnant women about ANC so that pregnant women know more about the meaning, benefits and goals of ANC and motivate pregnant women to comply with ANC.